Gongying-Jiedu-Xiji recipe promotes the healing of venous ulcers by inhibiting ferroptosis via the CoQ-FSP1 axis - Lu, Yongpan; Zhao, Dejie; Liu, Ming; Cao, Guoqi; Liu, Chunyan; Yin, Siyuan; Song, Ru; Ma, Jiaxu; Sun, Rui; Wu, Zhenjie; Liu, Jian; Wang, Yibing (Frontiers in Pharmacology, 2023)
Objective: Gongying-Jiedu-Xiji recipe (DDL, batch number Z01080175) reduces body temperature, detoxifies, activates the blood circulation, reduces swelling, and dispels decay and pus. The aim of this study was to investigate the mechanism of action by which DDL functions in the treatment of venous ulcers (VUs). Methods: Normal tissues as well as VU tissues before and after DDL treatment were collected from nine VU patients in the hospital with ethical approval. These three tissues were subjected to Prussian blue iron staining, immunoblotting, immunohistochemistry, immunofluorescence, and qPCR to detect the expression of ferroptosis suppressor protein 1 (FSP1), coenzyme Q (CoQ), 4-hydroxynonenal (4-HNE), and glutathione peroxidase 4 (GPX4). After successful validation of the heme-induced human foreskin fibroblast (HFF) ferroptosis model, lyophilized DDL powder was added to the cells, and the cells were subjected to viability assays, immunoblotting, flow cytometry, glutathione (GSH) and malonaldehyde (MDA) assays, electron microscopy and qPCR assays. Results: Ferroptosis in VU tissues was stronger than that in normal tissues, and ferroptosis in VU tissues after DDL treatment was weaker than that before treatment. Inhibition of CoQ and FSP1 and transfection of FSP1 influenced the effects of DDL. Conclusions: Our results suggest that DDL may promote healing by attenuating ferroptosis in VUs and that DDL may promote VU healing by modulating the CoQ-FSP1 axis.